Economic Viability Analysis of Processed Dragon Fruit Products: A Case Study of Dragon Fruit Kimchi and Dragon Fruit Bread Stick - tophan, warintorn; Tophan, Warintorn; Supphunyakul, Nattiya; Intharathakul, Khunkanitt (Journal of KMITL Business school, 2024)
Due to the oversupply of dragon fruits and the resulting drop in prices, the large-scale dragon fruit agricultural enterprise in Rong Chik Subdistrict, Phu Ruea District, Loei Province, sought ways to increase the value of their produce by processing it into dragon fruit kimchi and dragon fruit bread stick. To assess whether these products are worth investing in, this research aims to analyze the economic viability of processed dragon fruit products. This quantitative research targeted 20 members of the dragon fruit agricultural enterprise in Rong Chik Subdistrict, Phu Ruea District, Loei Province, selected through purposive sampling. Data were collected using raw material records, production processes, and interviews. The analysis focused on costs, returns, breakeven points, payback periods, and the economic viability of both products through net present value, internal rate of return, and benefit-cost ratio at a discount rate of 4.34%. The results showed that, over a 5-year period, dragon fruit kimchi had an average cost of 54.22 Baht per jar, with a selling price of 109 Baht per jar. The breakeven point was 76 jars, and the payback period was 6 months. The net present value was 38,481.98 Baht, which is positive. The internal rate of return was 196%, exceeding the discount rate, and the benefit-cost ratio was 1.80, greater than 1. Meanwhile, dragon fruit bread stick had an average cost of 7.83 Baht per pack, with a selling price of 10 Baht per pack. The breakeven point was 3,122 packs, and the payback period was 8 months. The net present value was 33,776.32 Baht, which is positive. The internal rate of return was 120%, exceeding the discount rate, and the benefit-cost ratio was 1.21, greater than 1. Therefore, both products were found to be economically viable. However, it should be noted that this assessment was based on a dragon fruit price of 7 Baht per kilogram. If the price increases, the potential risk due to higher production costs should be considered.